Predict New Therapeutic Drugs for Hepatocellular Carcinoma Based on Gene Mutation and Expression - Yu, Liang; Xu, Fengdan; Gao, Lin (Frontiers in Bioengineering and Biotechnology, 2020)
Hepatocellular carcinoma (HCC) is the most common primary liver malignancy and is a leading cause of cancer-related death worldwide. However, cure is not possible with currently used therapies, and there is not so much approved targeted therapy for HCC despite numerous attempts and clinical trials. So, it is essential to identify additional therapeutic strategies to block the growth of HCC tumors. We seek to use a systematic drug repositioning bioinformatics approach to identify novel candidate drugs to treat HCC, which considers not only aberrant genomic information, but also the changes of transcriptional landscapes. First, we screen the collection of HCC feature genes that frequently mutated in most samples of HCC based on human mutation data. Then, the gene expression data of HCC in TCGA are combined to classify the kernel genes of HCC. Finally, the therapeutic score (TS) of each drug is calculated based on the kolmogorov-smirnov statistical method. Using this strategy, we identified five drugs that associated with HCC, including three drugs that could treat HCC and two drugs that might have side-effect on HCC. In addition, we also make Connectivity Map (CMap) profiles similarity analysis and KEGG enrichment analysis on drug targets. All these findings suggest that our approach is effective for accurate discovering novel therapeutic options for HCC and easily to be extended to other tumors.